Blockchain Application in Fishery Supply Chain - Bhand, Aarohi Somnath; Bharsakale, Pranjal; Deshmane, Swaraj; Mali, Manisha (Journal of Trends in Computer Science and Smart Technology, 2024)
With 1.07% of the country’s overall GDP coming from fishing, the fishing industry has huge significance in India. The supply chain and overall exports to foreign nations will be improved by revolutionizing this sector of the economy. Consumers are nowadays very much concerned about their health and in knowing about the quality of the goods they purchase or consume, particularly when it comes to nutrition. Fish must be consumed within a certain time frame and under the right circumstances because it is a perishable food. The government officials must also keep an eye on illicit fishing, which is another serious problem that disrupts ecosystems in many different places. In other words, consumers, the government, and society in general demand transparency throughout the entire value chain of fish products. In this research, the use of blockchain using Ethereum-based smart contracts to trace fish packages back and forth throughout the entire fisheries value chain is explored.